Fabrication of phenyl boronic acid modified pH-responsive zinc oxide nanoparticles as targeted delivery of chrysin on human A549 cells. (2022) - Mahalanobish, Sushweta; Kundu, Mousumi; Ghosh, Sumit; Das, Joydeep; Sil, Parames C.
Abstract: Recently, different natural bioactive compounds have been used as anticancer agents for their various therapeutic benefits and non-toxic nature to other organs. However, they have various restrictions in preclinical and clinical studies due to their non-targeting nature and insufficient bioavailability. As a result, a zinc oxide nanoparticle (ZnO) based drug delivery medium was constructed which has good bio-compatibility and bio-degradability. It also displays cancer cell-specific drug delivery in a targeted and controlled way. In the present study, phenylboronic acid (PBA) tagged ZnO nanoparticles (ZnO-PBA) was fabricated and in the next step, chrysin (a natural bio-active molecule) was loaded to it to form the nanoconjugate (ZnO-PBA-Chry). Different characterization techniques were used to confirm the successful fabrication of ZnO-PBA-Chry. PBA-tagging to the nanoparticle helps in targeted delivery of chrysin in lung cancer cells (A549) as PBA binds with sialic acid receptors which are over-expressed on the surface of A549 cells. As ZnO dissociates in acidic pH, it shows stimuli-responsive release of chrysin in tumor microenvironment. Application of ZnO-PBA-Chry nanohybrid in lung cancer cell line A549 caused oxidative stress mediated intrinsic cell death and cell cycle arrest. ZnO-PBA-Chry downregulated MMP-2 and VE-Cadherin, thereby inhibiting metastasis and the invasive property of A549 cells. Graphical Abstract: ga1 Highlights: pH-responsive PBA functionalized ZnO nanoparticle was fabricated. Chrysin was loaded as a bioactive anticancer agent into ZnO nanoparticle. ZnO-PBA-Chry induced intrinsic cell death and cell cycle arrest in A549 cells. It inhibited metastasis and invasive properties of A549 cells.